Table 1_Equine-assisted learning and leadership transformation: an exploratory qualitative study of workplace behavior.docx - Rubentheran Sivagurunathan (22678700) (2025)
Background This study explores how equine-assisted leadership development (EALD) interventions activate experiential processes that reshape leaders’ self-concept, relational schemas, and behaviors. A conceptual model is proposed to explain how non-verbal interaction with horses catalyzes transformational learning. Methods A qualitative exploratory design was employed to examine leaders’ experiences over 12 months following reintegration into their workplaces. Eight leaders (n = 8) attended a 5-day EALD program, engaging in “join-up” exercises with horses. Data were analyzed through reflexive thematic analysis to identify leadership learning and transformation patterns. Findings The reflexive thematic analysis produced three interrelated themes: (1) embodied self-awareness and leadership reflection, (2) transformative learning and behavioral change, and (3) relational leadership and trust-based engagement—which together describe a developmental pathway from immediate embodied feedback to sustained workplace change. Originality/value This is the first Malaysian study to show how structured human–animal interaction can elicit sustained leadership shifts. By positioning horses as non-verbal feedback systems, the research highlights embodied, affective, and relational dimensions of leadership development often overlooked in cognitive or skills-based models.